THE ROLE OF THE PARLIAMENT IN ENSURING NATIONAL SECURITY IN USA AND EUROPEAN COUNTRIES (COMPARATIVE LEGAL ANALYSIS) - Khalikov Sarvar Mingishovich (Scholar Express Journals, 2022)
This article talks about the role of the parliament in foreign countries in the issue of ensuring national security, their comparative legal analysis. Indeed, the parliament plays an important role in supporting democratic traditions and the process of civil control, ensuring the smooth functioning of the institutional system of public administration. In many countries, the parliament is often seen as the official body that controls the executive and brings the president's proposals into line with the provisions of the country's basic law
Keywords: Institution Of Parliament; provisions; country; law